2010
DOI: 10.1038/ja.2010.16
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of plasmid-mediated quinolone-resistance determinants in Shigella flexneri isolates from Anhui Province, China

Abstract: Quinolones are used extensively to treat Shigella flexneri infection, and plasmid-mediated quinolone resistance (PMQR) determinants were recently reported. A total of 26 S. flexneri isolates collected from Anhui province, China, in 2005 were screened for PMQR determinants, bla gene, gyrA and parC genes, by PCR and sequencing. PMQR determinants were present in 53.8% (14 of 26) of isolates and qnrA 1 , qnrS 1 , qnrS 2 , aac(6¢)-Ib-cr and qepA were present in 30.8, 11.5, 3.8, 19.2 and 11.5% of those isolates, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…This result is consistent with the study from some Chinese cities/provinces, such as Henan 5 , Anhui 13 , and Hangzhou 7 where IIDSPCP was also implemented by the government. However, our results implied that the same or even more attention should be given to school-age children not attending school, since they have become the noticeable infected occupational group in Guangzhou, a trend that appears to have increased over the years.…”
supporting
confidence: 91%
“…This result is consistent with the study from some Chinese cities/provinces, such as Henan 5 , Anhui 13 , and Hangzhou 7 where IIDSPCP was also implemented by the government. However, our results implied that the same or even more attention should be given to school-age children not attending school, since they have become the noticeable infected occupational group in Guangzhou, a trend that appears to have increased over the years.…”
supporting
confidence: 91%
“…qnrS was the most frequent allele (4/125, 3.2 %) of the qnr genes, followed by qnrB, which was identified in two (1.6 %) of the 125 S. flexneri isolates. However, qnrA, which was reported to be the most common qnr allele among the S. flexneri isolates in China (Xiong et al, 2010), was not found. In this study, all three qnrS2-positive isolates belonged to PFGE cluster B, indicating that clonal spread was responsible for the dissemination of the qnrS2 gene amongst the S. flexneri isolates.…”
Section: Jmm Correspondencementioning
confidence: 85%
“…Quinolones are among the most important antibacterial agents used extensively for the treatment of shigellosis. Recently, quinolone resistance has been rising among Shigella isolates (Xiong et al, 2010). Quinolone resistance mainly results from chromosomal mutations in the quinolone resistance-determining regions (QRDRs) of DNA gyrase and topoisomerase IV (Dutta et al, 2005).…”
Section: Jmm Correspondencementioning
confidence: 99%
See 1 more Smart Citation
“…All of these belonged to the bla CTX-M-2 group (1). In 2004, a bla TEM-116 isolate from Zhengzhou, Henan Province, China, was obtained from a chicken (10), and human bla CTX strains were isolated in 2005 from Anhui Province, China (29). In 2006, four cases of shigellosis due to isolates harboring bla CTX-M-15 were described in New Zealand (25).…”
Section: Discussionmentioning
confidence: 99%